Age-Related Increase in Blood Levels of Otolin-1 in Humans. Issue 6 (July 2017) - Tabtabai, Ryan; Haynes, Laura; Kuchel, George A.; Parham, Kourosh
Abstract : Objective: To test the hypothesis that age-related demineralization of otoconia will result in an age-related increase in blood levels of otoconia matrix protein, otolin-1. Study Design: Cross-sectional observational clinical trial. Setting: Clinical research center. Patients: Seventy nine men and women ranging in age from 22 to 95 years old. Interventions: Diagnostic. Main Outcome Measures: Blood levels of otolin-1 in relation to age. Results: Levels of otolin-1 of subjects divided into four age groups (1: 20–30 [n = 20], 2: 50–65 [n = 20], 3: 66–80 [n = 20], 4: 81–95 [n = 19] years old) demonstrated an increasing trend with age. The difference between otolin levels of groups 2 and 3, as well as, ( p = 0.04) and 2 and 4 ( p = 0.031) were statistically significant, but there was no significant difference between the two oldest groups. Conclusions: Otolin-1 blood levels are significantly higher in patients older than 65 years of age. This is consistent with previous scanning electron microscopy findings of age-related otoconia degeneration and increased prevalence of benign paroxysmal positional vertigo (BPPV) with age. Normative data provided here can serve as important reference values against which levels from BPPV patients can be compared with further evaluate otolin-1 as a circulatory biomarker for otoconia degeneration.